Physiological and morphological characterization of american oil palms (elaeis oleifera hbk cortes) and their hybrids (elaeis oleifera × elaeis guineensis) on the indupalma plantation (2013)
The morphological and photosynthetic activity were characterizedin six genotypes of American oil palm (E. oleifera) ofdifferent origins and three of their OxG hybrids (E. oleifera × E.guineensis) with a completely randomized experimental design,three replications and 16 palms per replication. Determinationswere made for: photosynthesis, internal CO2 concentration,chlorophyll content, stomatal openings and density, specific leafarea, and measurements of vegetative growth. The genotypeswere differentiated by growth rate, emission, area and dryweight of the leaves. The stomatal openings of all the genotypeswere maximum in the morning hours, with partial closures atmidday; therefore, the maximum rate of photosynthesis wasbetween 9:00 and 12:00 hr. The ‘Perú’ American oil palm and‘hybrid 2’ (Sinú-Coarí × La Mé) showed higher CO2 internalconcentrations, total chlorophyll contents, light saturationpoints and photosynthetic rates, even with low levels of photosyntheticallyactive radiation; characteristics that indicatea high capacity for the fixation of CO2. The photosyntheticrate showed a high positive correlation with the chlorophyllcontent and a negative correlation with the specific leaf area.In conclusion, the ‘Perú’ American oil palm showed relevantcharacteristics for use in breeding programs as female parentof OxG hybrids, while ‘hybrid 2’, due to its outstanding morphophysiologicalcharacteristics, is considered a genotype withgood agronomic performance.